Design, Synthesis, and Evaluation of Anticonvulsant Activities of New Triazolopyrimidine Derivatives - Song, Mingxia; Zhao, Wennan; Zhu, Yangnv; Liu, Wenli; Deng, Xianqing; Huang, Yushan (Frontiers in Chemistry, 2022)
Epilepsy, a severe brain disease affecting a large population, is treated mainly by antiepileptic drugs (AEDs). However, toxicity, intolerance, and low efficiency of the available AEDs have prompted the continual attempts the discovery of new AEDs. In this study, we discovered a skeleton of triazolopyrimidine for the development of new AEDs. The design, synthesis, in vivo anticonvulsant activity evaluation of triazolopyrimidines (3a-3i, 6a-6e) and pyrazolopyrimidines (4a-4i) were reported. We found that most triazolopyrimidines showed anticonvulsive activity in the maximal electroshock (MES) and pentetrazol (PTZ)-induced seizure models. On the contrary, pyrazolopyrimidines (4a-4i) showed weak or no protective effects. Among the tested derivatives, compound 6d, holding a median effective dose (ED50) of 15.8 and 14.1 mg/kg against MES and PTZ-induced seizures respectively, was found to be the most potent one. Moreover, the protection index (PI) value of 6d was significantly higher than that of the available AEDs such as valproate, carbamazepine, and diazepam. The antiepileptic efficacy of compound 6d was also observed in the 3-mercaptopropionic acid and bicuculline-induced seizure models. Antagonistic effects of flumazenil and 3-MP for the anticonvulsive activity of 6d, and also the radioligand-binding assay confirmed the involvement of GABA receptors, at least benzodiazepine (BZD) receptor, in the anticonvulsant activity of compound 6d. Docking study of compounds 4e and 6d with GABAA receptor confirmed and explained their affinity to the BZD receptors.